Electrospinning of nanofibers: Potentials and perspectives for active food packaging - Zhang, Cen; Li, Yang; Wang, Peng; Zhang, Hui (Comprehensive reviews in food science and food safety, 2020)
Electrospun nanofibers with structural and functional advantages have drawn much attention due to their potential applications for active food packaging. The traditional role of food packaging is just storage containers for food products. The changes of retailing practice and consumer demand promote the development of active packaging to improve the safety, quality, and shelf life of the packaged foods. To develop the technique of electrospinning for active food packaging, electrospun nanofibers have been covalently or non‐covalently functionalized for loading diverse bioactive compounds including antimicrobial agents, antioxidant agents, oxygen scavengers, carbon dioxide emitters, and ethylene scavengers. The aim of this review is to present a concise but comprehensive summary on the progress of electrospinning techniques for active food packaging. Emphasis is placed on the tunability of the electrospinning technique, which achieves the modification of fiber composition, orientation, and architecture. Efforts are also made to provide functionalized strategies of electrospun polymeric nanofibers for food packaging application. Furthermore, the existing limitations and prospects for developing electrospinning in food packaging area are discussed.